The relationship between women’s body mass index and breast cancer outcomes was U-shaped - Wei, Wensong; Wei, Suosu; Huang, Zhen; Zhang, Qiuhuan; Liu, Fei; Xie, Yujie; Wei, Jing; Mo, Chongde; Zhou, Ying; Qin, Shengpeng; Zou, Quanqing; Yang, Jianrong (Frontiers in Oncology, 2023)
Background Several studies have analyzed the relationship between body mass index (BMI) and the prognosis of breast cancer (BC). However, whether their relationship is linear or curvilinear remains unclear. This cohort study examined the specific relationship between BMI and BC outcomes. Methods This retrospective cohort study included 1049 BC patients from March 7, 2013 through December 31, 2019 in a hospital. Kaplan-Meier curves, multivariate Cox proportional models, and restricted cubic spline (RCS) was used to analysis the relationship between BMI and overall survival (OS) and breast cancer-specific survival (BCSS) was analyzed. Results During a median of 4.87 (IQR:3.26-6.84) years of follow-up period, 71 patients (6.77%) died, of which 50 (70.42%) were attributed to BC. RCS analysis revealed a U- shaped relationship between BMI levels and OS and BCSS after adjusting for other variables. The turning points of the U-shaped curves were 23 kg/m2. On the left side of the turning point, the risk of OS (HR, 0.83; 95% CI, 0.70, 0.98) and BCSS (HR, 0.80; 95% CI, 0.65, 0.98) were adversely correlated with BMI. In contrast, to the right of the turning point, the risk of OS (HR, 1.22; 95% CI, 1.10, 1.37) and BCSS (HR, 1.28; 95% CI, 1.13, 1.46) was positively related to BMI. Kaplan-Meier curves and multivariate Cox regression analyses shown consistent results with RCS analyses. Conclusion BMI was an independent prognostic factor for BC, and had a U-shaped relationship with OS and BCSS. Interventions should be designed to improve patient outcomes based on BMI.